Jensen’s problem of governance revisited by the relative age effect on spanish football - Torres-Pruñonosa, Jose; Burillo, Pablo; Fernández-Luna, Álvaro; Pérez-González, Benito (Cultura, Ciencia Y Deporte, 2026)
This study analyses Jensen's problem of governance by examining the Relative Age Effect (thereinafter RAE) on Spanish Football. We analysed the players of thetop eight Spanish football academies (n=736). Four of the academies belong to clubs and four to Sport Stock Corporations (SSCs), all of them are playing in the top tierof Spanish football. We used the Poisson Regression analysis to identify the presence of the relative age effect. The existence of RAE is found to be significant (p<.001)in both clubs and SSCs. According to Jensen's governance theory, SSCs should be more efficient, and therefore the starting hypothesis would be that they would notbe affected by the RAE bias whereas clubs should. The results of the study refute Jensen's problem of governance and are a new contribution to the stakeholder’stheory. Policymakers should consider governance reforms, such as hybrid multi-stakeholder models, to counteract RAE. It is also evident that the RAE is a bias thatnotably affects football academies and other sports with a lot of participants.
EL PROBLEMA DE GOBERNANZA DE JENSEN REVISITADO PORELEFECTODELAEDADRELATIVAENELFÚTBOLESPAÑOL
Este estudio analiza el problema de la gobernanza de Jensen examinando el Efecto de la Edad Relativa (RAE) en el fútbol español. Hemos analizado los jugadoresde las ocho mejores academias de fútbol españolas (n= 736). Cuatro de las academias pertenecen a clubes y cuatro a Sociedades Anónimas Deportivas (SAD) y todasellas juegan en la máxima categoría del fútbol español. Utilizamos la regresión de Poisson para identificar la presencia del RAE. La existencia de RAE es significativa(p<0.001) tanto en clubes como en las SADs. Según la teoría de la gobernanza de Jensen, las SADs deberían ser más eficientes, dado que la hipótesis de partidaes que no se ven afectadas por el sesgo del RAE, mientras que los clubes sí. Los resultados del estudio refutan el problema de gobernanza de Jensen y constituyenuna nueva aportación a la teoría de los stakeholders. Los responsables políticos deberían considerar reformas de gobernanza, como modelos híbridos con múltiplesstakeholders, para contrarrestar el RAE. También se pone de manifiesto que el RAE es un sesgo que afecta notablemente a las academias de fútbol y a otros deportes con muchos participantes.
Keywords: football academies; Jensen’s governance problem; sport stock corporations; talent identification; theory of stakeholders; academias de futbol; identificación del talent; problema de gobernanza de Jensen; sociedades anónimas deportivas; teoría de los stakeholders